Penerapan Metode Clark And Wright dan Pure Strategy dalam Menentukan Strategi Pemasaran dan Distribusi Produk Roti - Dhimas Igo Pratomo Putro Haniswanto; Agustian Suseno; Dimas Nurwinata Rinaldi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Having a competitive strategy in the current era is the main key for companies to compete. The importance of having a strategy in quality that exists in products and an optimal distribution system is one way for CV XYZ to face competition. Therefore, this study aims to determine the competitive strategy of bakery products using game theory and to obtain the optimal distribution route using Clark and Wright. The pure strategy from game theory can identify the strategies used by each player, namely the Rasa strategy for stuffed bread and the Resilience strategy for bread. In addition, the Clark and Wright method can save 13.45 km of distance and fuel costs per week of IDR 118,957,-/day from the previously used route. By getting the results of competitive strategies and optimum distribution routes, this study can provide suggestions to CV XYZ regarding strategies to maintain its competitiveness.